(untitled) (Web of Discoveries: Journal of Analysis and Inventions, 2025)
Phraseological units with somatic components (body parts) are widely used in many languages, reflecting cultural perceptions and human experiences. This article explores the similarities and differences between English and Uzbek phraseological units that include somatic elements, such as head, hand, eye, and heart. The study aims to analyze the semantic meanings and cultural implications of these expressions in both languages.